Use of complementary and alternative medicine in the management of sickle cell disease: Complementary and alternative medicine in sickle cell - Lubega, Martin; Namayanja, Dianah Mubiru; Nuwabaine, Lillian; Nakitto, Asia (Chronic Diseases Journal, 2023)
BACKGROUND: Sickle cell disease (SCD) is the most prevalent genetic hemoglobinopathy with an estimated 300,000 babies born with the disease globally every year. Due to the chronic nature of the disease, there is a pressing need for safe, effective, and affordable therapeutic agents for SCD. In many settings, use of complementary and alternative medicine (CAM) has been reported in the management of the disease. However, there is limited documentation about the use of CAM among patients with SCD in Uganda. Thus, this study was conducted with the aim to determine the prevalence of CAM use and the most commonly used CAM among patients with SCD at Mulago Sickle Cell Clinic (MSCC). METHODS: This cross-sectional study was conducted for a period of 3 months using an interviewer-administered questionnaire to collect data from 293 participants who were recruited into the study using simple random sampling method at Mulago National Referral Hospital Sickle Cell Clinic, Uganda. The collected data were analyzed using SPSS software to express univariate data as median, mean, mode, percentage, and frequency tables and graphs. RESULTS: CAM use was reported among 76.7% of the participants with the majority using more than on type of CAM. Biological products were the most commonly used form of CAM followed by spiritual healing; 74.6% of the CAM users used biological products, 25.2% used spiritual healing and prayer, while 0.6% used energy therapies. The most commonly used CAM include avocado leaves (50.9%), herbal concoctions (28.3%), beetroot (19.8%), prayer (18.8%), garlic (13.7%), and anointed water (12.6%). CONCLUSION: This study found a high prevalence of CAM use among patients with SCD.